PENGARUH GROSS PROFIT MARGIN, EARNING PER SHARE, NET PROFIT MARGIN, DAN UMUR PERUSAHAAN TERHADAP HARGA SAHAM - Nicholas Nicholas; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this study was to determine the effect of Gross Profit Margin, Earning Per Share, Net Profit Margin, Firm Age on Stock Price. The sample in this study amounted to 36 nickel sub sector mining companies listed on the Indonesia Stock Exchange in 2020-2024. The sampling technique used in this study was purposive sampling with multiple linear regression analysis methods and using the SPSS version 20.0 program. The results of this study indicate that simultaneously the variables Gross Profit Margin, Earning Per Share, Net Profit Margin, Firm Age affect the Stock Price. While partially Gross Profit Margin, Net Profit Margin, and Company Age have no effect on Stock Prices.